Genetic Diversity Analysis of 14 Potato Genotypes Based on Morphological Characters and SSR Markers - Kristianto Nugroho; Rerenstradika T. Terriyana; Kusmana Kusmana; Puji Lestari; I Made Tasma (Jurnal AgroBiogen, 2019)
Potato is one of important carbohydrate sources used as an alternative crop in Indonesia. The challenges in national potato breeding program included low productivity, less tolerance to environmental stresses, and narrow genetic diversity. The purpose of this study was to analyze genetic diversity of 14 potato genotypes based on morphological characters and SSR markers newly developed from genome sequences of Indonesian potato genotypes. Principal component analysis of morphological data was done using program XLSTAT. DNA of 14 potato genotypes were assayed using 22 SSR markers. Phylogenetic tree was constructed using program NTSYS version 2.1. The PCA showed that leaf shape, leaf color, tuber shape, tuber skin color, and tuber color contributed most to the total diversity. SSR polymorphism analysis demonstrated that as many as 196 alleles were detected in this study. The average allele number was 8.9 ranged from 5 to 13 alleles per locus. The average major allele frequencies was 22% ranged from 14 to 43%. Gene diversity ranged from 0.70 to 0.92 with the average of 0.86, meanwhile the heterozigosity observed ranged from 0 to 0.71 with the average of 0.05. Phylogenetic analysis generated two main clusters in the coefficient of similarity 0.77. The first cluster consisted of three genotypes while the second cluster consisted of eleven genotypes. The new developed SSR markers used in this study were able to differentiate potato accessions having similar morphological characters but were different genetically. The results of this study should be useful in assessing genetic materials in potato cultivar development program.